Osteopromotion Capacity of Bovine Cortical Membranes in Critical Defects of Rat Calvaria: Histological and Immunohistochemical Analysis - Danieletto-Zanna, Carolina Ferrairo; Bizelli, Vinícius Ferreira; Ramires, Guilherme André Del Arco; Francatti, Tamires Melo; Carvalho, Paulo Sérgio Perri de; Bassi, Ana Paula Farnezi (International Journal of Biomaterials, 2020)
Membranes that aid the guided bone regeneration (GBR) process have been the subject of studies of compatible biomaterials that contribute to this repair process. The present study compared different membranes used in critical-size defects of rat calvaria by assessing GBR as well as histological, histomorphometric, and immunohistochemical reactions. Forty-eight male albino Wistar rats were randomly allocated into four groups (n = 12 each), namely, C: membrane-free control group (only blood clot, negative control group); BG: porcine collagen membrane group (Bio-Gide®, positive control group); GD: bovine cortical membrane group (first experimental group); and GDF: thicker bovine cortical membrane group (second experimental group). Rats were euthanized at 30 and 60 days postoperatively. Quantitative data from the histometric analysis were submitted to two-way ANOVA and Tukey’s posttest when p<0.05. Histomorphometric results of the thicker bovine cortical membrane at 30 and 60 days were promising, showing improved new bone formation values (p<0.05), and the CD group presented similar results in both analysis periods, being surpassed only by the GDF group (p<0.05). The immunohistochemical results were associated with the histomorphometric data. A less-thick membrane also assisted in GBR. All membranes promoted GBR, especially the positive control and experimental groups.